Ultrafast optical spectroscopy of strongly correlated materials and high-temperature superconductors: a non-equilibrium approach. Issue 2 (3rd March 2016) - Giannetti, Claudio; Capone, Massimo; Fausti, Daniele; Fabrizio, Michele; Parmigiani, Fulvio; Mihailovic, Dragan
Abstract : In the last two decades non-equilibrium spectroscopies have evolved from avant-garde studies to crucial tools for expanding our understanding of the physics of strongly correlated materials. The possibility of obtaining simultaneously spectroscopic and temporal information has led to insights that are complementary to (and in several cases beyond) those attainable by studying the matter at equilibrium. From this perspective, multiple phase transitions and new orders arising from competing interactions are benchmark examples where the interplay among electrons, lattice and spin dynamics can be disentangled because of the different timescales that characterize the recovery of the initial ground state. For example, the nature of the broken-symmetry phases and of the bosonic excitations that mediate the electronic interactions, eventually leading to superconductivity or other exotic states, can be revealed by observing the sub-picosecond dynamics of impulsively excited states. Furthermore, recent experimental and theoretical developments have made it possible to monitor the time-evolution of both the single-particle and collective excitations under extreme conditions, such as those arising from strong and selective photo-stimulation. These developments are opening the way for new, non-equilibrium phenomena that can eventually be induced and manipulated by short laser pulses. Here, we review the most recent achievements in the experimental and theoretical studies of the non-equilibrium electronic, optical, structural and magnetic properties of correlated materials. The focus will be mainly on the prototypical case of correlated oxides that exhibit unconventional superconductivity or other exotic phases. The discussion will also extend to other topical systems, such as iron-based and organic superconductors, and charge-transfer insulators. With this review, the dramatically growing demand for novel experimental tools and theoretical methods, models and concepts, will clearly emerge. In particular, the necessity of extending the actual experimental capabilities and the numerical and analytic tools to microscopically treat the non-equilibrium phenomena beyond the simple phenomenological approaches represents one of the most challenging new frontiers in physics.